Effects of gum chewing on recovery of bowel function following cesarean section: a randomized controlled trial - Jakkaew B. (2014)
Purpose: To evaluate the effects of gum chewing on recovery of bowel function after cesarean section. Methods: Fifty pregnant women who underwent cesarean section at Chiang Mai University hospital from September 2010 to December 2010 were recruited. After cesarean section, patients were randomized into two groups. In group 1 (conventional), patients were fed according to conventional feeding protocol without gum chewing. For group 2 (gum chewing), patients were asked to chew two pieces of sugarless gum for 30 min in the morning, noon, evening and bedtime until the first flatus, along with conventional postoperative feeding protocol. Categorical variables were analyzed using the Chi-square or Fischer's exact test, as appropriate. For continuous variables with skewed distribution, the Mann-Whitney U test was employed. Results: There were 25 patients in each group. Median time to the first flatus was shorter in the gum chewing group (36.37 vs. 41.33 h, P = 0.02). Also, there was a trend toward less abdominal cramping on days 1 and 2 in the gum chewing group. However, no difference in other outcome measures of bowel function recovery and ileus-related complications between the groups could be demonstrated. Approximately three-fourth of the women in each group had good tolerance to their first meal. Hospital stay and participants' satisfaction to the assigned feeding schedules were comparable between the study groups. Conclusion: Gum chewing is associated with faster recovery of bowel function following cesarean section. It is safe, practical, inexpensive, and well tolerated. © 2013 Springer-Verlag Berlin Heidelberg.